# Mobius Transformations

Prove that if T is a Mobius transformation such that T(0) = 0, then T may be written as T(z) = z/(cz+d) for some choices of c and d.

© BrainMass Inc. brainmass.com June 3, 2020, 8:05 pm ad1c9bdddfhttps://brainmass.com/math/complex-analysis/sample-mobius-transformations-123077

#### Solution Preview

General Mobius transformation is T = (az+b)/(cz+d), where

ad-bc not= 0 ...

#### Solution Summary

A Mobius transformation is investigated. The solution is detailed and well presented.

$2.19